An Optimal Solution to Multi-Goal Fuzzy Linear Programming Problems Using Elementary Transformations - Shrivastava, Arti; Saxena, Bharti; Rathore , Vandana; Bhardwaj, Ramakant (Communications in Mathematics and Applications, 2024)
This article explores how to solve multipurpose problems to obtain optimal solutions using fuzzy linear programming. Our goal is to minimize production and transportation costs by using the most basic transportation methods and comparing the results to conventional methods. We discuss the results of numerical examples and illustrate this method.